Diagnóstico de calidad para la conservación en espacios agrícolas en terrazas. Propuesta metodológica para la cuenca del Guiniguada (Gran Canaria, Islas Canarias) - Romero Martín, L. E.; Ruiz Flaño, P.; Hernández Calvento, L. (Geographicalia, 2016)
In the present text it’s exposed the designed method to set up the ranges of quality for the conservation of a hundred of unit of landscape where the presence of terraces is dominant. This rnethod value the characteristics of those unit relative of it’s worth in productivity, ecology and scenery. The obtained results show that in the half and low areas of the Guiniguada valley, the spaces occupied by terraces present between a medium and high levels of quality for the conservation. 71% of the units are qualified by some one of these two categories, a high number bearing in mind that 60% of them are abandoned.